2012
DOI: 10.1155/2012/723418
|View full text |Cite
|
Sign up to set email alerts
|

Transoesophageal Echocardiography for Monitoring Liver Surgery: Data from a Pilot Study

Abstract: A pilot study aimed to introduce intraoperative monitoring of liver surgery using transoesophageal echocardiography (TEE) is described. A set of TEE measurements was established as a protocol, consisting of left atrial (LA) dimension at the aortic valve plane; mitral velocity flow integral, calculation of stroke volume and cardiac output (CO); mitral annular plane systolic excursion; finally, right atrial area. A total of 165 measurements (on 21 patients) were performed, 31 occurring during hypotension. The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…7-9 These findings often impact on patient management. 8 In this case, early placement (as opposed to rescue placement after the cardiac arrest occurred) allowed rapid diagnosis of PAE as a rare cause of cardiac arrest and contributed to improved cardiac and neurological outcome by expediting management.…”
Section: Discussionmentioning
confidence: 99%
“…7-9 These findings often impact on patient management. 8 In this case, early placement (as opposed to rescue placement after the cardiac arrest occurred) allowed rapid diagnosis of PAE as a rare cause of cardiac arrest and contributed to improved cardiac and neurological outcome by expediting management.…”
Section: Discussionmentioning
confidence: 99%
“…Pissarra et al [46] performed 165 measurements (on 21 patients), 31 occurring during hypotension. They concluded that during acute blood loss LA dimensions changed earlier than CVP, and, in one patient, a dynamic left ventricular (LV) obstruction was observed.…”
Section: Tee In Liver Surgerymentioning
confidence: 99%
“…TEE accurately measures the left atrial (LA) dimension at the aortic valve plane, mitral flow velocity integral, calculation of stroke volume and cardiac output (CO), mitral annular plane systolic excursion and right atrial area [1,2]. Pissarra et al [46] performed 165 measurements (on 21 patients), 31 occurring during hypotension. They concluded that during acute blood loss LA dimensions changed earlier than CVP, and, in one patient, a dynamic left ventricular (LV) obstruction was observed.…”
Section: Tee In Liver Surgerymentioning
confidence: 99%